2020
DOI: 10.1080/13607863.2020.1786799
|View full text |Cite
|
Sign up to set email alerts
|

Very frequent physical aggression and vocalizations in nursing home residents with dementia

Abstract: Objectives: We investigated the 2-week prevalence and correlates of very frequent physical aggression (PA) and vocalizations in nursing home (NH)-residents with dementia. Method/Design: This cross-sectional study used combined data of 2074 NH-residents from four studies, collected from 119 dementia special care units in 26 Dutch NH. Very frequent PA was defined as scoring 6 or 7 on the items 'hitting', pushing', 'biting' and 'kicking' of the Cohen Mansfield Agitation Inventory; very frequent vocalizations as s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 61 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…In their seven-tiered model of the severity and prevalence of challenging behavior, Brodaty et al categorise extreme challenging behavior as Tier 7, with an estimated prevalence described as rare [4]. In our WAALBED (WAAL-Behavior-in-Dementia)-III study, similar two-week prevalence rates of 7.4% of very frequent agitation, 2.2% of very frequent physical aggression and 11.5% of very frequent vocalizations were found [5,6]. Previous studies have shown that challenging behavior has a great influence on the residents and their environment (relatives, nursing home staff and other residents), especially in case of aggression [8][9][10].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…In their seven-tiered model of the severity and prevalence of challenging behavior, Brodaty et al categorise extreme challenging behavior as Tier 7, with an estimated prevalence described as rare [4]. In our WAALBED (WAAL-Behavior-in-Dementia)-III study, similar two-week prevalence rates of 7.4% of very frequent agitation, 2.2% of very frequent physical aggression and 11.5% of very frequent vocalizations were found [5,6]. Previous studies have shown that challenging behavior has a great influence on the residents and their environment (relatives, nursing home staff and other residents), especially in case of aggression [8][9][10].…”
Section: Introductionsupporting
confidence: 56%
“…This explorative, qualitative study was performed as a distinct part of the WAALBED-III study that focused on nursing home residents with dementia and extreme challenging behavior [5,6,14]. Because of the lack of a theoretical frame to explain why situations of extreme challenging behavior in nursing home residents with dementia are experienced as an impasse, we decided to apply qualitative methods in this study.…”
Section: Study Aim Design Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with multiple studies in residents with dementia measuring sleep disturbances on the NPI sleep item. 14,43,44 In our qualitative study, 15 staff described resident agitation as both a cause and consequence of sleep disturbances, as agitation may be why residents sleep badly but they may be agitated for other reasons, such as pain, 45 which could also contribute to poor sleep. 46 Agitation and quality of life are highly correlated in the MARQUE cohort study 16 and a previous study in Japanese care home residents found sleep disturbances on the NPI sleep item associated with lower quality of life.…”
Section: Discussionmentioning
confidence: 91%
“…Terms such as aggressive, disturbing, problematic, disruptive behaviors, and restlessness have been used in other research on this topic [ 8 , 9 ]. Older age, functional impairment [ 10 ], and declining cognitive function influence and aggravate agitated behaviors [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%